Sukuk: The post-issuance effect on firm’s value / Zaimi Mohamed, Mohd Husnin Mat Yusof and Wan Mansor Wan Mahmood - Mohamed, Zaimi; Mat Yusof, Mohd Husnin; Wan Mahmood, Wan Mansor (2012)
This study examines the financial performance of firms subsequent to the introduction of sukuk in their capital mix. A group of sukuk offerings by Malaysian companies was identified primarily from the Securities Commission, while financial information was obtained directly from companies financial reports. In addition to the liquidity and leverage ratios, the presence of the new source of funds in the company’s capital structure was defined as i- ratio. Another variable known as i-factor was also introduced to represent the intensity of newly issued sukuk as a percentage of company’s total debt prior to the offerings. Based on the data for the period from January 2001 to December 2006, the results show that firm’s liquidity and leverage position do influence company’s financial performance subsequent to the issuance. In addition, the newly introduced variables, the i-ratio and i- factor, also indicate their relationships towards firm’s value. It seems that Malaysian companies are showing continuous support in sukuk as a medium to purify their source of funds. Continuous investigations on this type of instrument will further strengthen the presence of Islamic finance and banking industry in the country while providing valuable information to potential market players.